Extension summer courses on ethnic groups and Health at School of Public Health of USP, or the difference that needs to make a difference - Adorno, Rubens de Camargo Ferreira; Oliveira, Lavínia Santos de Souza (Saúde e Sociedade, 2007)
This report discusses the introduction of the conceps of race, ethnics and ethnicity in Brazilian public health policies highlighting the relationships between ethnicity and universal social policies, departing from universities extension courses in public health.